2018
DOI: 10.1093/humupd/dmy006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of monozygotic twinning in ART: a systematic review and a meta-analysis

Abstract: We found blastocyst transfer to be a risk factor for MZT. Hence, the results of this meta-analysis may weaken the previously proposed view that greater experience with blastocyst transfer and improved culture media could decrease the high rate of MZT after blastocyst transfer. To minimize the rate of MZT and the associated complications, the mechanisms underlying blastocyst transfer and MZT pregnancy must be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 50 publications
3
62
1
2
Order By: Relevance
“…There has been consistent evidence of a higher risk of monozygotic twinning following ART compared with natural conception, 1.4% following ART versus 0.4% following natural conception; the high incidence with ART is in agreement with current study findings . This increased risk has been attributed to various underlying factors and processes involved in ART, such as ICSI, assisted hatching, embryo biopsy for pre‐implantation genetic testing for aneuploidies (PGT‐A), monogenic disorders (PGT‐M) and structural chromosomal rearrangements (PGT‐SR), extended embryo culture and embryo cryopreservation . Studies have shown a consistent association between extended embryo culture and embryo splitting .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…There has been consistent evidence of a higher risk of monozygotic twinning following ART compared with natural conception, 1.4% following ART versus 0.4% following natural conception; the high incidence with ART is in agreement with current study findings . This increased risk has been attributed to various underlying factors and processes involved in ART, such as ICSI, assisted hatching, embryo biopsy for pre‐implantation genetic testing for aneuploidies (PGT‐A), monogenic disorders (PGT‐M) and structural chromosomal rearrangements (PGT‐SR), extended embryo culture and embryo cryopreservation . Studies have shown a consistent association between extended embryo culture and embryo splitting .…”
Section: Discussionsupporting
confidence: 87%
“…18,19 This increased risk has been attributed to various underlying factors and processes involved in ART, such as ICSI, assisted hatching, embryo biopsy for pre-implantation genetic testing for aneuploidies (PGT-A), monogenic disorders (PGT-M) and structural chromosomal rearrangements (PGT-SR), extended embryo culture and embryo cryopreservation. 1,4,6,20 Studies have shown a consistent association between extended embryo culture and embryo splitting. 10,21,22 There have been very few studies addressing whether embryo biopsy is a risk factor for monozygotic twinning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Proposed triggers for splitting include gene mutations, abnormalities in cell surface proteins, and abnormalities in the formation of the zona pellucida (Kilby et al, ; Mercan et al, ; Jim and Berkovich, ). Increased frequency of monozygotic twins is observed after infertility therapy such as intracytoplasmic sperm injection (Sills et al, ; Song et al, ; Hviid et al, ), indicating a possible association of zona pellucida damage and monozygotic twinning. Enders () described that one possible cause for the increase in monozygotic twinning following in vitro fertilization such as assisted hatching is the constriction of the inner cell mass during mechanical hatching of the blastocyst from the zona pellucida as opposed to the natural digesting that occurs in vivo.…”
Section: Etiology and Pathogenesis Of Conjoined Twinsmentioning
confidence: 99%